Ethnobotany for food security and ecological transition: wild food plant gathering and consumption among four cultural groups in Kurram District, NW Pakistan - Sayed Taufiq Hussain; Sayed Muhammad; Sheharyar Khan; Wahid Hussain; Andrea Pieroni (BMC, 2023)
Abstract Background In traditional food systems, especially those of rural populations around the world, wild food plants remain crucial. These resources need to be urgently documented to lay the foundations for sustainable livelihoods and food security. Methods In the present field study, we gathered information about wild food plants and mushrooms consumed by four ethnic groups (Turis, Khushis, Hazaras, and Christians) living in Kurram District, NW Pakistan, by conducting semi-structured interviews and holding group discussions. Results A total of 57 wild edible plants and mushrooms were reported, with the documented taxa belonging to 50 genera and 34 families. Turis reported the highest number of wild food plants (41), followed by Hazaras (37), Khushis (35), and then Christians, who reported only 11 plants. The most dominant families were Rosaceae, followed by Polygonaceae, Brassicaceae, Fabaceae, Lamiaceae, Moraceae, and Plantaginaceae. The comparative analysis we conducted with the pre-existing Pakistani ethnobotanical studies revealed that 23 wild edible plants have not been previously reported as food items in the area under study, which included Fragaria nubicola, Lepidium draba, Pinus wallichiana, Podophyllum emodi, Prunus jacquemontii, Sambucus nigra, Sideroxylon mascatense, and Thymus linearis. Four wild edible mushrooms are also reported for the area for the first time: Calvatia gigantea, Morchella esculenta, Pisolithus albus, and Tulostoma squamosum. The cross-cultural analysis of wild edible plants and their uses revealed remarkable similarity between Khushis and Hazaras. The overlapping pattern of wild edible plant use among these two groups, as well as Turis, confirms the existence of cross-cultural interactions among these communities, which have shared the same environmental and socio-cultural space for several decades. Food heritage and some unique dishes are linked to wild edible plants in the area, such as Zamda, prepared by Turis, and Saba, famous among Khushis and Hazaras. Conclusion This study suggests that some wild edible plants could be cultivated to protect a few threatened species from overexploitation, while the overall wild food plant heritage should be promoted and revitalized; for example, within educational platforms aimed at improving the wellbeing of local communities and the global ecological transition we must deal with.